Odpowiedź :
Odpowiedź:
a)
[tex]\frac{5x - 3}{4}[/tex] + 3 = 2x | *4
5x - 3 + 12 = 8x
-3 + 12 = 8x - 5x
9 = 3x | :3
3 = x
x = 3
b)
x - [tex]\frac{2x + 3}{5}[/tex] = 3 |*5
5x -(2x + 3) = 15
5x - 2x - 3 = 15
3x = 18 |:3
x = 6
c)
4 -[tex]\frac{x}{4}[/tex] = 2x - [tex]\frac{1}{2}[/tex] |*4
16 - x = 8x - 2
16 + 2 = x + 8x
18 = 9x |:9
2 = x
x = 2
d)
[tex]\frac{2x}{3}[/tex] + 4 = [tex]\frac{x+2}{3}[/tex] |*3
2x + 12 = x + 2
2x - x = -12 + 2
x = -10
e)
[tex]\frac{3x-2}{5}[/tex] - 2 = [tex]\frac{x}{5}[/tex] |*5
3x - 2 - 2 = x
3x - x = 4
2x = 4 |:2
x = 2
Powodzenia dalej! :)
Szczegółowe wyjaśnienie: